EXAMINING COMMUNICATION MEDIATION MODEL ON YOUTH ONLINE POLITICAL ENGAGEMENT - Hasbullah Azis; Pawito Pawito; Agung Satyawan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Using a communication mediation model, the present study tested the influencing factor of social media utilization on the political engagement on social media. Through O-S-O-R model proposed by McLeod, Kosicki, and McLeod, this study tested the correlation between pre-exposure (motivation) – Stimulus (media social use) – post-exposure orientation (political efficacy) – Response (political engagement) in the context of Chinese youth of Singkawang. By analyzing the Pearson correlation and linear regression of 125 respondents collected through a questionnaire, this model resulted in several findings, for example, motivation had a relationship with the use of social media for political information purposes where social utility motives had a more significant effect than other motives. The use of political information media had an influence on an individual's internal and collective efficacy rather than external efficacy. Political efficacy generated by the use of social media had an influence on the political engagement of Singkawang Chinese youth even though external efficacy was deemed a negative predictor of political engagement.